Respuestas
Respuesta dada por:
1
Respuesta:
[ (senx+cosx) · (sen²x - senx·cosx + cos²x)] ² - 2· sen³x · cos³x =
(senx+cosx)² ·(1- senx·cosx)² - 2· sen³x· cos³x =
(sen²x+cos²x+2·senx·cosx) ·(1- senx·cosx)² - 2· sen³x· cos³x =
(1+2·senx·cosx)·(1-2·senx·cosx + sen²x·cos²x) - 2· sen³x· cos³x =
(1+2·senx·cosx)·(1-2·senx·cosx) + (1+2·senx·cosx)·(sen²x·cos²x) - 2· sen³x· cos³x =
1-4·sen²x·cos²x + sen²x·cos²x + 2· sen³x· cos³x - 2· sen³x· cos³x =
1- 3·sen²x· cos²x
Explicación paso a paso:
Preguntas similares
hace 4 años
hace 4 años
hace 6 años
hace 6 años
hace 8 años
hace 8 años